Coconut Shell Charcoal Adsorbent with Variations in Activation to Reduce BOD (Biochemical Oxygen Demand) and TSS (Total Suspended Solid) Levels in Liquid Tofu Waste: Adsorben Arang Tempurung Kelapa dengan Variasi Aktivasi dalam Menurunkan Kadar BOD (Biochemical Oxygen Demand) dan TSS (Total Suspended Solid) pada Limbah Cair Tahu - Azmi, Nabilah Nur; Adzillah, Ing Wilma Nurrul; Ratnawati, Kania (Media Ilmiah Teknik Lingkungan (MITL), 2025)
Wastewater from tofu production conntains high concentrations of organic matter, particularly Biochemical Oxygen Demand (BOD) and Total Suspended Solids (TSS). Without proper treatment, this waste has the potential to pollute surrounding water bodies and harm aquatic ecosystems. This research explores the use of coconut shell charcoal as a natural adsorbent to reduce BOD and TSS levels in tofu wastewater. The charcoal was physically activated by heating it at 105°C for three different durations: 15, 60, and 180 minutes. This treatment aimed to improve its surface area and porosity, enhancing its adsorption capacity. Laboratory analysis showed a significant decrease in both BOD and TSS, with the highest efficiency observed at 180 minutes of activation. These findings suggest that coconut shell charcal, a widely available and underutilized material, can serve as an effective and environmentally friendly option for simple wastewater treatment at a local level.